Dopamine-induced interlayer bridging for enhanced through-plane thermal conductive performance of expanded graphite-based thermal interface materials - Yuyuan Fan; Long Gao; Jinxing Liu; Yajuan Zhong; Sufang Yang; Xueyao Feng; Hongtao Yu; Junfen Li; Xiaodong Tian; Lei Zheng; Xing Guo; Xi Yan; et al. (Chemical Engineering Journal, 2026)

Effect of Guide Vane Case on Hydrodynamic Performance and Unsteady Pressure-Pulsation Characteristics of Shaftless Pump-Jet Thruster - Taofeng Wang; Sanming Song; Liming Li; Jinxing Yu; Kaizhou Liu; Adam Rushworth; Xisheng Feng (Journal of Marine Science and Engineering, 2026)
Propulsors are essential power units for underwater vehicles and major sources of self-noise, with unsteady pressure pulsations linked to flow-induced noise. To study the impact of guide vane case on the hydrodynamic performance and pressure pulsation of a shaftless pump-jet thruster, six guide vane configurations were first compared under a reference operating condition of 600 rpm: a vaneless baseline, fixed vertical guide vanes, fixed forward-inclined guide vanes, fixed reverse-inclined guide vanes, co-rotating guide vanes, and counter-rotating guide vanes. Based on this comparison, the vertical-vane and counter-rotating-vane configurations were selected for extended operating-condition analysis under three rotational speeds and three inflow conditions. Transient numerical simulations were conducted using the SST k−ω turbulence model. The rotating regions were defined in a rotating reference frame, and the unsteady rotor–stator interaction was resolved using a transient sliding-mesh interface. Results show that the counter-rotating guide vane configuration achieves the highest head and efficiency among the tested cases, with a head of 1.8955 m and efficiency of 0.7306, representing increases of 19.64% and 22.87% over the fixed vertical guide vane case. The fixed forward-inclined guide vane exhibits the strongest thrust fluctuation and pressure pulsation. Pressure-pulsation intensity generally decreases from the impeller rim toward the central axis. Frequency-domain results indicate that most cases are dominated by the blade-passing frequency, whereas the counter-rotating guide vanes show a response nearly twice this frequency.

Interpretable machine learning for exploring multiple influencing factors of PM2.5 and their interaction effects - Qiyuan Yang; Jie Gao; Jinxin Chen; Tong Ma; Han Xu; Feng Wang; Yuting Wei; Jinxing Liu; Qian Sun; Yinchang Feng; Guoliang Shi (Journal of Environmental Sciences, 2026)

Multi-pathway vegetation restoration drives differential carbon sequestration regulated by hydrogeological conditions in Lijiang River Basin - Shumin Feng; Xiuqin Wu; Jianhua Cao; Hui Yang; Fen Huang; Liankai Zhang; Jinxing Zhou (CATENA, 2026)

Experimental and numerical investigation on the rotational resistance behavior of aluminum alloy insert hub joints - Jinxing Feng; Zhenggang Cao; Xiao Hu; Yifan Ding; Feng Fan (Engineering Structures, 2025)

Ensemble source apportionment of particulate matter and volatile organic compounds and quantifying ensemble source impacts on ozone - Weiqing Liang; Zhenyu Wang; Dongheng Zhao; Jinxing Liu; Tong Ma; Yinchang Feng; Guoliang Shi (Journal of Environmental Sciences, 2025)

Highly efficient electrochemical reduction of nitrate to ammonia by a CuO-Co3O4 composite membrane electrode - Yufeng Wu; Shiyang Feng; Kui Yang; Wenjian Yang; Chao Li; Xuejun Cui; Jinxing Ma (Chemical Engineering Journal, 2025)

β-Hydroxybutyrate ameliorated metabolic dysfunction and improved synaptic integrity via AKT signaling in an LPS-induced depression mice model - Shengnan Mou; Tahir Ali; Li Ling; Jinxing Feng; Shupeng Li (Food Bioscience, 2025)

Pentoxifylline Prevents Neuroinflammation and Modifies PTEN/TrkB Signaling in an LPS-Induced Depression Model - Tahir Ali; Yanhua Luo; Chengyou Zheng; Shafiq Ur Rahman; Iram Murtaza; Jinxing Feng; Shupeng Li (Journal of Neuroimmune Pharmacology, 2025)

Sources, calculation methods, and reduction strategies for GHG emissions at ports: current status and future trends - Jinxing Shen; Wenlong Gao; Jingwei Lu; Fengjiang Li; Xuejun Feng (Frontiers in Marine Science, 2025)
Greenhouse gas (GHG) emissions from ports have gained increasing attention due to their significant impact on climate change. Nevertheless, the existing research in this domain remains fragmented, with limited generalizable findings. To address this gap, an integrative framework is proposed in this study to systematically review the literature and identify future research directions. Using the Web of Science database, a bibliometric analysis of 230 documents and an in-depth review of 68 studies are conducted, focusing on emission sources, emission calculations, and abatement technologies. Key findings can be drawn as follows: (1) Research on port-related GHG emissions has expanded rapidly since the Paris Agreement, but international collaboration and institutional coordination remain insufficient, hindering the development of comprehensive solutions. (2) Inconsistent classification of GHG emission sources across studies leads to biases and limits comparability. Reclassifying emissions based on equipment operation locations could improve both accuracy and cross-study alignment. (3) Activity-based approaches are the primary methods for emissions assessment but heavily rely on static emission factor datasets, particularly for container ports. Expanding these datasets for diverse port types, updating localized factors in real-time, and integrating alternative energy sources can enhance adaptability and accuracy. (4) Current mitigation strategies focus on technological innovations, energy substitution, and operational optimization. However, limitations such as high implementation costs, slow commercialization, and insufficient policy support continue to impede progress. To achieve zero-carbon port operations, future research should prioritize the integration of technical innovations with economic and policy frameworks. A multidisciplinary approach is essential for overcoming current barriers and promoting sustainable practices in port management.

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Hourly PM2.5 concentration prediction for dry bulk port clusters considering spatiotemporal correlation: A novel deep learning blending ensemble model - Jinxing Shen; Qinxin Liu; Xuejun Feng (Journal of Environmental Management, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Whether the green credit policy effectively promote green transition of enterprises in China? Empirical analysis and mechanism verification - Shujing Zhang; Rui Dong; Jinxing Jiang; Shuyu Yang; Javier Cifuentes-Faura; Sihan Peng; Yanchao Feng (Environmental Research, 2024)

scFED: Clustering Identifying Cell Types of scRNA-Seq Data Based on Feature Engineering Denoising - Yang Liu; Feng Li; Junliang Shang; Jinxing Liu; Juan Wang; Daohui Ge (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Machine learning reveals the effects of drivers on PM2.5 and CO2 based on ensemble source apportionment method - Han Xu; Yi Ge; Chun Zhang; Zhenyu Wang; Bo Xu; Huan Zhao; Junbo Huang; Gen Wang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Research, 2023)

Experimental study on the collapse evolution law of unlined tunnel in Boulder-Cobble mixed formation - Yiwen Qin; Jinxing Lai; Xiaoyong Cao; Wenbo Zan; Zhihua Feng; Yongli Xie; Weimin Zhang (Tunnelling and Underground Space Technology, 2023)

Ibrutinib Delays ALS Installation and Increases Survival of SOD1G93A Mice by Modulating PI3K/mTOR/Akt Signaling - Chengyou Zheng; Weifen Li; Tahir Ali; Ziting Peng; Jieli Liu; Zhengying Pan; Jinxing Feng; Shupeng Li (Journal of Neuroimmune Pharmacology, 2023)

Lacticaseibacillus paracasei K56 Attenuates High-Fat Diet-Induced Obesity by Modulating the Gut Microbiota in Mice - Zhonghua Miao; Hanying Zheng; Wei-Hsien Liu; Ruyue Cheng; Hui Lan; Ting Sun; Wen Zhao; Jinxing Li; Xi Shen; Hongwei Li; Haotian Feng; Wei-Lian Hung; et al. (Probiotics and Antimicrobial Proteins, 2023)

Cu(II) removal from water by trimercapto-s-triazine trisodium salt modified alkaline lignin - Qiaorui Wang; Fei He; Jinxing Gu; Xuqin Song; Feng Xu (Environmental Science and Pollution Research, 2023)

Overexpression of maize GOLDEN2 in rice and maize calli improves regeneration by activating chloroplast development - Wanni Luo; Jiantao Tan; Tie Li; Ziting Feng; Zhi Ding; Xianrong Xie; Yuanling Chen; Letian Chen; Yao-Guang Liu; Qinlong Zhu; Jinxing Guo (Science China Life Sciences, 2023)

MgIn2S4@In2O3 hierarchical tubular heterostructures with expedited photocarrier separation for efficient visible-light-driven antimicrobial activity - Jinxing Yu; Peiyi Yan; Feng Chen; Shu Jin; Xiaoxiang Xu; Jun Qian (Chemical Engineering Journal, 2023)

scVAEBGM: Clustering Analysis of Single-Cell ATAC-seq Data Using a Deep Generative Model - Hongyu Duan; Feng Li; Junliang Shang; Jinxing Liu; Yan Li; Xikui Liu (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Simulation study of rockfall deposition based on UAV-PCAS-PFC: a case study on the rockfall deposition of Xiaomaopo in Kaiyang County - Jinxing Xu; Genlan Yang; Yigen Qin; Feng Liang (Arabian Journal of Geosciences, 2022)

Age-dependent microRNAs in regulation of vascular cambium activity in Chinese fir (Cunninghamia lanceolata) - Guijun Liu; Xian Xue; Jinling Feng; Dechang Cao; Jinxing Lin; Huimin Xu (Trees, 2021)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

Comparative transcript profiling and cytological observation of the newly bred recessive genic male sterility non-heading Chinese cabbage (Brassica rapa ssp. chinensis) line WS24-3A - Liping Song; Xia Li; Feng Zu; Changbin Gao; Bincai Wang; Chufa Lin; Jinxing Tu; Aihua Wang; Guolin Zhou (Genes & Genomics, 2019)

Identification of a nuclear-recessive gene locus for male sterility on A2 chromosome using the Brassica 60 K SNP array in non-heading Chinese cabbage - Xia Li; Aihua Wang; Feng Zu; Zhenhua Hu; Jiazao Lin; Guolin Zhou; Jinxing Tu (Genes & Genomics, 2016)

Mapping of BnMs4 and BnRf to a common microsyntenic region of Arabidopsis thaliana chromosome 3 using intron polymorphism markers - Shengqian Xia; Ling Cheng; Feng Zu; Xiaoling Dun; Zhengfu Zhou; Bin Yi; Jing Wen; Chaozhi Ma; Jinxiong Shen; Jinxing Tu; Tingdong Fu (Theoretical and Applied Genetics, 2012)

Study of Lead Level During Pregnancy by Application of Synchrotron Radiation Micro XRF - Yongpeng Tong; Huibin Sun; Qi Luo; Jinxing Feng; Xiaohong Liu; Feng Liang; Fen Yan; Ke Yang; Xiaohan Yu; Yulan Li; Jianmin Chen (Biological Trace Element Research, 2011)

The speed of mitochondrial movement is regulated by the cytoskeleton and myosin in Picea wilsonii pollen tubes - Maozhong Zheng; Qinli Wang; Yan Teng; Xiaohua Wang; Feng Wang; Tong Chen; Jozef Šamaj; Jinxing Lin; David C. Logan (Planta, 2010)